Ultra-sensitive and selective quantification of endothelin-1 in human plasma using ultra-performance liquid chromatography coupled to tandem mass spectrometry - Suzuki, Yosuke; Witt, Lukas; Mier, Walter; Mikus, Gerd; Markert, Christoph; Haefeli, Walter E.; Burhenne, Jürgen (Journal of pharmaceutical and biomedical analysis, 2017)
Endothelin-1 (ET-1) is a potent endogenous vasoconstrictor peptide and the plasma concentrations are commonly quantified by immunoassays such as enzyme-linked immuno-sorbent assays (ELISA) with the disadvantage of possible cross-reactivity with closely related endothelin derivatives. The aim of this study was to develop and validate an ultra-sensitive and selective assay for the quantification of ET-1 in human plasma, using ultra-performance liquid chromatography with tandem mass spectrometry (UPLC-MS/MS) after solid phase extraction. The assay fulfilled the requirements of the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) guidelines for assay validation, with a lower limit of quantification of 1.5pg/mL for ET-1. Recovery rates from plasma ranged between 80.8% and 93.6%, and matrix effect varied between 121% and 135%. The assay was successfully applied to assess the time course of plasma ET-1 concentrations in two human volunteers after co-administration of bosentan and clarithromycin. In this trial, the concentrations measured by UPLC-MS/MS were slightly lower than those measured by ELISA, with a strong positive correlation between the two methods. Our novel UPLC-MS/MS method is applicable to the clinical setting and may have better selectivity for ET-1 than ELISA.